Strengthening the management of emergency nurses to reduce the incidence of nurse-patient conflicts (加强急诊护理人员自我管理降低护患冲突发生率) - HE Zhiqiang (何志强); LIU Jian (刘建); CHEN Xuemei (陈雪妹) (中西医结合护理)
This paper briefly analyzed the potential factors of nurse-patient conflicts, and discussed the ways of strengthening the management of emergency nurses and reducing the incidence of nurse-patient conflicts. (本文简要分析护患冲突的影响因素, 探讨医护人员如何通过自我管理降低护患冲突发生率, 构建和谐护患关系。)